THE RELATIONSHIP BETWEEN SELF EFFICACY AND EARTHQUAKE AND TSUNAMI DISASTER PREPAREDNESS AMONG STUDENTS OF SMAN 13 BANDA ACEH - Desreza, Nanda; Nursa’adah; Anisa, Rina (Transpublika Publisher, 2023)
Disaster is often perceived as uncontrollable things. Self-efficacy has been identified in having significant influence toward behavior in facing uncontrollable problems. School is one of the areas that have a higher risk of casualties during earthquake and tsunami because it is a gathering place of students, teachers, and other academic members especially on school hours; Therefore, they need the preparedness to face the disaster. The purpose of this research is to understand the correlation between self-efficacy and disaster preparedness of earthquake and tsunami on students at State Senior High School 13 of Banda Aceh. The type of the research is descriptive-correlative method with a cross-sectional study design. The sampling technique used is total sampling. The instrument used is a questionnaire which is self-efficacy questionnaire and preparedness questionnaire that develop by LIPI-UNESCO/ISDR. The data analysis used in this research was Spearman’s Correlation. This research shows that there is a significant correlation between self-efficacy and disaster preparedness on students at State Senior High School 13 of Banda Aceh. The data analysis shows that p-value of self-efficacy (0.001) including dimension of level (0.007), dimension of strength (0.002), dimension of generalization (0.001). Schools are recommended to improve students’ self-efficacy with disaster preparedness simulation training of earthquake and tsunami.